The ionic reordering in Fe-Ti ferrimagnetics as a dominant source of the reversed RM in basaltic rocks - ORLICKÝ, Oto (Contributions to Geophysics and Geodesy, 2009)
The basalts of the Pleistocene to Quaternary age from southern part of Slovakia were investigated. These are the basalts containing predominantly the titano- maghemites (Ti-Mgh-es) which carry the reversed remanent magnetization (RM). The partial thermoremanent magnetization (PTRM) in original and artiﬁcially prepared sam- ples was induced in the geomagnetic ﬁeld of normal polarity and intensity H ≈ 48μT. The PTRM reversed by the self-reversed mechanism was induced in all the above-mentioned types of basalts, in the interval 300 to 475 °C. In this temperature interval an increase of magnetic susceptibility with a peak about 450 °C was detected. The acquired reversed RM and PTRM of basalts have been explained on the basis of the reordering of magnetic ions in the A and B sub-lattices of the oxidized Fe-Ti ferrimagnetics in basalts.